Immediate Neural Plasticity Involving Reaction Time in a Saccadic Eye Movement Task is Intact in Children With Fetal Alcohol Spectrum Disorder. (22nd September 2016) - Paolozza, Angelina; Munoz, Douglas P.; Brien, Donald; Reynolds, James N.
Abstract : Background: Saccades are rapid eye movements that bring an image of interest onto the retina. Previous research has found that in healthy individuals performing eye movement tasks, the location of a previous visual target can influence performance of the saccade on the next trial. This rapid behavioral adaptation represents a form of immediate neural plasticity within the saccadic circuitry. Our studies have shown that children with fetal alcohol spectrum disorder (FASD) are impaired on multiple saccade measures. We therefore investigated these previous trial effects in typically developing children and children with FASD to measure sensory neural plasticity and how these effects vary with age and pathology. Methods: Both typically developing control children ( n  = 102; mean age = 10.54 ± 3.25; 48 males) and children with FASD ( n  = 66; mean age = 11.85 ± 3.42; 35 males) were recruited from 5 sites across Canada. Each child performed a visually guided saccade task. Reaction time and saccade amplitude were analyzed and then assessed based on the previous trial. Results: There was a robust previous trial effect for both reaction time and amplitude, with both the control and FASD groups displaying faster reaction times and smaller saccades during alternation trials (visual target presented on the opposite side to the previous trial). Children with FASD exhibited smaller overall mean amplitude and smaller amplitude selectively on alternation trials compared with controls. The effect of the previous trial on reaction time and amplitude did not differ across childhood and adolescent development. Conclusions: Children with FASD did not display any significant reaction time differences, despite exhibiting numerous deficits in motor and higher level cognitive control over saccades in other studies. These results suggest that this form of immediate neural plasticity in response to sensory information before saccade initiation remains intact in children with FASD. In contrast, the previous trial effect on amplitude suggests that the motor component of saccades may be affected, signifying differential vulnerability to prenatal alcohol exposure. Abstract : In individuals performing eye movement tasks, the location of a previous visual target can influence performance on the next trial, representing a form of immediate neural plasticity. In this study, the previous trial effect on reaction time was not different in children with FASD, suggesting that immediate neural plasticity in response to sensory information remains intact. In contrast, the previous trial effect on amplitude suggests that the motor component of eye movements may be differentially vulnerable to prenatal alcohol exposure.